The Role of Law in Tackling Climate Change: Policy and Implementation in Various Countries - Loso Judijanto; Kurshed Aqbil Nyham; Asfahani Asfahani; Arief Fahmi Lubis (Edujavare Publishing, 2024)
This study investigates the critical role of law in addressing climate change, focusing on various countries' policy and implementation frameworks. By employing a normative approach, the research examines how different nations integrate legal principles such as justice, equity, and sustainability into their climate strategies. It provides a comparative analysis of developed and developing countries, highlighting the diverse legislative measures adopted to mitigate greenhouse gas emissions and promote renewable energy. The study reveals significant disparities in enforcement and compliance mechanisms, emphasizing the importance of robust legal institutions and governance structures for effective climate action. It identifies innovative legal solutions and best practices, such as Denmark's Climate Act and Costa Rica's decarbonization policies, which offer valuable insights for global climate governance. Despite progress, the research underscores persistent challenges, particularly in developing countries, where policy fragmentation and limited resources impede implementation. The findings highlight the need for enhanced international cooperation, capacity-building, and financial support to strengthen climate laws worldwide. This study contributes to the broader discourse on climate change law, offering recommendations for more effective and equitable legal frameworks to tackle this global crisis.